2006
DOI: 10.1074/jbc.m601914200
|View full text |Cite
|
Sign up to set email alerts
|

PfPKB, a Protein Kinase B-like Enzyme from Plasmodium falciparum

Abstract: Intracellular cell signaling cascades of protozoan parasitePlasmodium falciparum are not clearly understood. We have reported previously (Kumar, A., Vaid, A., Syin, C., and Sharma, P. (2004) J. Biol. Chem. 279, 24255-24264) the identification and characterization of a protein kinase B-like enzyme in P. falciparum (PfPKB). PfPKB lacks the phosphoinositide-interacting pleckstrin homology domain present in mammalian protein kinase B. Therefore, the mechanism of PfPKB regulation was expected to be different from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 29 publications
2
29
0
Order By: Relevance
“…falciparum Cultures-P. falciparum 3D7 strain was cultured at 37°C in RPMI 1640 medium, supplemented either with 0.5% Albumax II (Invitrogen) or 10% ABϩ human serum as described earlier (12,17). For sexual stage studies, 3D7A, a variant of P. falciparum strain 3D7, was used to obtain gametocyte-enriched culture as described previously (18).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…falciparum Cultures-P. falciparum 3D7 strain was cultured at 37°C in RPMI 1640 medium, supplemented either with 0.5% Albumax II (Invitrogen) or 10% ABϩ human serum as described earlier (12,17). For sexual stage studies, 3D7A, a variant of P. falciparum strain 3D7, was used to obtain gametocyte-enriched culture as described previously (18).…”
Section: Methodsmentioning
confidence: 99%
“…Detailed understanding of calcium-mediated signaling pathways could provide insights into novel molecular mechanisms involved in parasite development. For instance, calcium regulation of a protein kinase B-like enzyme (12) via calmodulin seems to be important for erythrocyte invasion (8). Plasmodium contains calciumdependent protein kinases (CDPKs) (13), which have been found only in plants and some protists but are absent from almost all metazoans (14).…”
mentioning
confidence: 99%
“…It has also been reported that cytosolic Ca 2ϩ increases in free merozoites in response to the change in K ϩ ion concentration when they are released from the red blood cell (9). This Ca 2ϩ increase and the PfPKB activation are both blocked by the PLC inhibitor U73122 (9,31,32), implying that PLC/IP 3 -dependent Ca 2ϩ signaling may also be active during the late schizont and merozoite stage of the P. falciparum lifecycle, albeit activated by different extracellular signals. In our experiments we were not able to measure Ca 2ϩ signals in intraerythrocytic segmented (late phase) schizonts (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…It was recently reported that parasite egress from erythrocytes depends on the calcium-dependent protein kinase PfCDPK5 (33) a process that occurs during late schizgony. Moreover, another calcium-dependent kinase, PfPKB, is believed to be involved in the reinvasion of erythrocytes by the released merozoites (31,32). It has also been reported that cytosolic Ca 2ϩ increases in free merozoites in response to the change in K ϩ ion concentration when they are released from the red blood cell (9).…”
Section: Discussionmentioning
confidence: 99%
“…At their destination, they support intensified binding of the merozoite to the RBC as well as its reorientation prior to RBC invasion (reviewed in Cowman et al, 2012;Cowman and Crabb, 2006). Inhibition of PI-PLC with the commercial PLC inhibitor U73122 prevents calcium-mediated signaling and thus activation of the plasmodial protein kinase B by calmodulin, in consequence impairing secretion of micronemal proteins (Raabe et al, 2011a(Raabe et al, , 2011bSingh et al, 2010;Vaid et al, 2008;Vaid and Sharma, 2006). The plasmodial PI-PLC is also involved in the signaling pathways initiating gametogenesis, as was shown for P. berghei and P. falciparum (reviewed in Bennink et al, 2016;Kuehn and Pradel, 2010).…”
Section: The Role Of Plasmodial Phospholipases During Life-cycle Progmentioning
confidence: 99%